2023
DOI: 10.1101/2023.05.09.539963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunomodulatory Leptin Receptor+Sympathetic Perineurial Cells Protect Against Obesity by Facilitating Neuroendocrine-Mediated Brown Adipose Tissue Thermogenesis

Abstract: SummaryAdipose tissues (ATs) are innervated by sympathetic nerves, which drive reduction of fat mass via lipolysis and thermogenesis. Here, we report a population of immunomodulatory leptin receptor (LepR)-expressing barrier cells which ensheath sympathetic axon bundles in adipose tissues. These LepR-expressing Sympathetic Perineurial Cells (SPCs) produce IL33, a factor for maintenance and recruitment of regulatory T cell (Treg) and eosinophils in AT. Brown adipose tissues (BAT) of mice lacking IL33 in SPCs (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Interestingly, upon tissue damage such as irradiation or chemotherapy requiring regeneration of hematopoietic stem cells, LEPRpositive mesenchymal cells differentiate into adipocytes which in turn produce KITL to enable a functional niche and support hematopoietic regeneration (30). Complementary mesenchymal and signaling components were recently shown to support normal tissue homeostasis and suppress inflammation in brown adipose tissue (BAT): LEPR-positive mesenchyme supports adaptive thermogenesis and restrains inflammation in BAT (23), while endothelial cell-derived KITL/SCF signals to KIT on brown adipocytes to promote homeostatic lipid accumulation when thermogenesis is inhibited (31). As the stellate cells under investigation in our study are also lipidstoring cells, these studies raise the possibility that lipid-storing stromal cells engage KITL signaling to promote tissue homeostasis and limit inflammation more broadly across organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, upon tissue damage such as irradiation or chemotherapy requiring regeneration of hematopoietic stem cells, LEPRpositive mesenchymal cells differentiate into adipocytes which in turn produce KITL to enable a functional niche and support hematopoietic regeneration (30). Complementary mesenchymal and signaling components were recently shown to support normal tissue homeostasis and suppress inflammation in brown adipose tissue (BAT): LEPR-positive mesenchyme supports adaptive thermogenesis and restrains inflammation in BAT (23), while endothelial cell-derived KITL/SCF signals to KIT on brown adipocytes to promote homeostatic lipid accumulation when thermogenesis is inhibited (31). As the stellate cells under investigation in our study are also lipidstoring cells, these studies raise the possibility that lipid-storing stromal cells engage KITL signaling to promote tissue homeostasis and limit inflammation more broadly across organs.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments focused on pancreatic stellate cells (PSCs), tissue-resident mesenchymal cells which serve as cells of origin for PDAC CAFs. We found that this mesenchymal lineage in normal human and murine pancreas tissue expresses KITL-this lineage has lipid storage capacity and co-expresses the leptin receptor (LEPR), with parallels to LEPR-positive mesenchyme previously implicated in tissue homeostasis in the bone marrow (22) and brown adipose tissue (23). Mesenchymal KITL expression is lost during tumor evolution and acquisition of a cancer-associated fibroblast (CAF) stromal phenotype, with functional significance for tissue state and tumorigenic potential.…”
Section: Introductionmentioning
confidence: 94%